2010
DOI: 10.1007/s00038-010-0195-7
|View full text |Cite
|
Sign up to set email alerts
|

Communication, social capital and workplace health management as determinants of the innovative climate in German banks

Abstract: ObjectiveThe present study aims to measure the determinants of the innovative climate in German banks with a focus on workplace health management (WHM).MethodsWe analyze the determinants of innovative climate with multiple regressions using a dataset based on standardized telephone interviews conducted with health promotion experts from 198 randomly selected German banks.ResultsThe regression analysis provided a good explanation of the variance in the dependent variable (R² = 55%). Communication climate (β = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…An interesting finding of the present study was the favorable psychosocial work environments were positively associated with WSC. Previous studies also found that organizational justice, quality leadership and open communication [ 35 , 36 , 54 ] were positively associated with WSC. A previous randomized intervention study among Chinese community health (CHC) centers [ 55 ] indicated that team-building courses for CHC directors (team management, communication skills, and practical team leadership experiences) and group psychological consultations (on topics including team communications and stress management) for CHC staff can improve workplace social capital.…”
Section: Discussionmentioning
confidence: 76%
“…An interesting finding of the present study was the favorable psychosocial work environments were positively associated with WSC. Previous studies also found that organizational justice, quality leadership and open communication [ 35 , 36 , 54 ] were positively associated with WSC. A previous randomized intervention study among Chinese community health (CHC) centers [ 55 ] indicated that team-building courses for CHC directors (team management, communication skills, and practical team leadership experiences) and group psychological consultations (on topics including team communications and stress management) for CHC staff can improve workplace social capital.…”
Section: Discussionmentioning
confidence: 76%
“…Cross-sectional studies examining the factors that determine an innovative workplace atmosphere identified a correlation between a better environment for communication and a more innovative workplace. 6 Thus, improving workers’ communication skills could potentially contribute to improving worker performance and productivity.…”
Section: Discussionmentioning
confidence: 99%
“… 1 5 Moreover, studies indicate that effective communication was associated with an innovative workplace environment. 6 In addition, a correlation between communication and work safety has been suggested. 7 …”
mentioning
confidence: 99%
“…27 In the literature, social capital is associated with both health 28-31 and employees' functioning. [32][33][34] In particular, bonding social capital is ascribed a health-related effect 35,36 and has meaningful business implications. 37 Organizational bonding social capital refers to mutual trust and cooperative relations between employees who are similar in terms of hierarchy and identity.…”
Section: Focus Of the Study And Theoretical Foundationmentioning
confidence: 99%